Assessing the Quality of Faculty Websites: A Case Study - Hristoski, Ilija; Velinov, Goran; Dimovski, Tome (University of Novi Sad, Technical faculty “Mihajlo Pupin”, Zrenjanin, Republic of Serbia, 2022)
For online organizations, websites play the role of digital storefronts and showrooms in the same way the physical storefronts and showrooms represent ‘mirror’ reflecting brick-andmortar companies. The website’s quality is an enormously important aspect since the website is often the first impression an organization gives to its online visitors, who can potentially become its customers. Wanting that first impression to be a good one is imperative not only to businesses and organizations, but also to faculties, universities, and other highereducational and research-oriented institutions. The paper aims to present a case study of how the students assessed the quality of their faculty website. Their perceptions about website quality have been drawn from four dimensions: performance, design, usability, and content. Based on an online survey containing questions addressing the most relevant aspects of these four dimensions, the data acquired from a representative sample has been subject to a factor analysis, which revealed significant insights into the most influential factors that underpin the faculty website quality. These represent a solid basis for the faculty management team while undertaking relevant measures to improve various faculty website quality aspects that can lead to increasing the satisfaction of online visitors, positive word-of-mouth spread, as well as improving faculty reputation and image in a long run.
Keywords: Website quality, factor analysis, faculty, assessment, case study, SPSS